The instruments and the results of the education of geoinformatics - Bornemisza, Imre (Acta Agraria Kaposváriensis, 2006)
At the Department of Information Technology and General Technology of the University of Pécs geoinformatics has been taught for years to students of teacher of technical skills. The task chosen for practical training has two goals: on the one hand, the students experience lifelike situations and gain knowledge to pass on, further more, the result of the accomplished project, i.e. the geoinformatics system will help the work of the botanical garden. The student group used in the last semester the GNU/Linux operation system and the GRASS GIS-software.